Research of Chinese Auspicious Elements in Tableware Design -Illustration with Chinese Auspicious Fish - Huang, Yue-Xin; Kang, BumKyu (International JOURNAL OF CONTENTS, 2013)
Chinese auspicious element is a kind of art which is used to express yearning of a happy life. It is one of the great treasures of China, with not only emotional value of the people but also an aesthetic value. Chinese auspicious element derives from the aspiration of luck, enthusiasm of life and conciseness of eliminating malicious. It is of great cultural connotation and widely used in interior design, graphic design, fashion design and such. There are many research papers on application methodology of auspicious elements; however, there are very limited research papers on three-dimension product, let alone application in tableware. This paper focuses on illustration of Chinese representative auspicious element “auspicious fish” in tableware design. The research of its application of auspicious element’s styling characteristics is of important significance in auspicious element spread and tableware design. This dissertation aims to provide referential design methodology and experience for later researches on related topic. KCI Citation Count: 0